Efeito dos fármacos ácido zoledrônico e sunitinibe sobre a vasculatura da maxila de ratos - Maccari, Giovana Prediger (2022)
Medication-related osteonecrosis of the jaw (MRONJ) is an adverse effect of antiresorptive and antiangiogenic drugs. It occurs mainly in patients undergoing intravenous bisphosphonate administration. Even though this adverse effect has been investigated since 2003, its etiopathogenesis has not still been completely understood. Several theories have been proposed, including the possible antiangiogenic effect of bisphosphonates being one of the factors responsible for the lesion development. The present study aimed to analyze the vasculature and the expression of VEGF (vascular endothelial growth factor) in the maxilla of rats treated with zoledronic acid and/or sunitinib. Wistar rats (n=52) were allocated into four groups according to the treatment administered: (1) Sunitinib (n=13); (2) Sunitinib/zoledronic acid (n=13); (3) Zoledronic acid (n=13); (4) Control group (n=13). After 15 days of treatment, the upper right molars were extracted. On postoperative day 21, animals were euthanized, and the maxillae were histomorphometrically analyzed. The proportion of blood vessels and VEGF expression were quantified in both sides of maxilla (tooth region and tooth extraction region). Alveolar bone, oral mucosa and dental pulp were the sites evaluated. In the tooth region, vessel quantification in the H&E analysis did not show significant differences between groups, whereas VEGF staining was less in the oral mucosa of the sunitinib/zoledronic acid group than in the control. In the tooth extraction region, vasculature in the oral mucosa was greater in the sunitinib and sunitinib/zoledronic acid groups than zoledronic acid group, with no significant difference from the control. Still in the tooth extraction region, vasculature was greater in the alveolar bone of the sunitinib compared to zoledronic acid group and VEGF staining was greater in the oral mucosa in the sunitinib group compared to control, whereas in the alveolar bone, it was greater in the control compared to all other groups. Conclusion: Zoledronic acid and sunitinib seem to have distinct effects on vasculature and VEGF expression according to the site of maxilla analyzed. VEGF immunostaining does not seem to represent the sunitinib antiangiogenic effect.